Effect Of Acid Treated Biochar On Urea Fertilizer For Retaining Ammonium And Nitrate Ions In Soil - Norazman, Farhaneem (2018)
Urea is widely used as fertilizer because it is inexpensive, economical to produce, soluble in water and contain high amount of nitrogen (47%). Biochar impregnated urea has the potential to improve nitrogen use efficiency of plant by reducing the N losses via gaseous emission of ammonia (NH3) and nitrous oxide (N_2O) to the atmosphere and nitrate leaching into surface and ground water bodies. The aim of this study is to investigate the biochar performance in reducing the loses of ammonium and nitrate ions by increasing its negative surface charge to improve its cation exchange capacity (CEC) which may influence its ability to retain the ions. The biochar was derived from rubber wood sawdust, underwent a pyrolysis process before treated with phosphoric acid at various concentration to improve its ion retention properties. From the optimization result obtained using response surface method regarding the acid treatment process, the best setting suggested for biochar was treatment with 1.5M phosphoric acid at 90°C. Confirmation runs obtained from the best setting were 7.06 pH with negative surface charge of 7.18 mmol/gram. Ammonium and nitrate retention in soil were measured and compared between ureas impregnated with acid treated and untreated biochars. Results showed that urea with acid treated biochar was able to retain 48.7% of ammonium and 45.2% of nitrate as compared to 44.7% and 28.0% shown by urea with untreated biochar, after week 3. This study affirms that acid treated biochar increases the ability of urea to retain more ammonium and nitrate compared to the untreated biochar.